Risk Categorization Predicts Disability in Pain-associated Functional Gastrointestinal Disorders After 6 Months. Issue 5 (May 2017) - Cunningham, Natoshia R.; Jagpal, Anjana; Peugh, James; Farrell, Michael K.; Cohen, Mitchell B.; Mezoff, Adam G.; Lynch-Jordan, Anne; Kashikar-Zuck, Susmita
ABSTRACT: Introduction: For a large portion of youth, pain-associated functional gastrointestinal disorders (FGIDs) are associated with significant impairment over time. Clinically feasible methods to categorize youth with FGIDs at greatest risk for persistent pain-related impairment have not yet been identified. Methods: Measures of functional disability, pain intensity, and anxiety were collected on 99 patients with FGIDs (ages 8–18) during a visit to a pediatric gastroenterology office to assess for the presence of risk. Follow-up data were obtained on a subset of this sample (n = 64) after 6 months, either in person or via mail. The present study examined whether a greater number of risk factors at baseline predicted greater pain-related disability at follow-up. Results: Patients were divided into 4 groups based on number of risk factors present at the initial assessment: 0 (18.2%), 1 (24.2%), 2 (26.3%), and 3 (31.3%). The presence of 2 or 3 risk factors significantly predicted greater disability at follow-up compared to those with 0 risk factors ( R 2  = 0.311) and those with just 1 risk factor (Cohen's d values of –1.07 and –1.44, respectively). Discussion: A simple approach to risk categorization can identify youth with FGIDs who are most likely to report increased levels of pain-related impairment over time. These findings have important clinical implications that support the utility of a brief screening process during medical care to inform referral for targeted treatment approaches to FGIDs.